2017
DOI: 10.21608/asnj.2017.58468
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nutritional Stunting and Associated Risk Factors among Under Five Children in Suhag Governorate

Abstract: Introduction : Nutritional stunting indicates the chronic restriction of a child potential growth, Aim: To assess the prevalence and associated risk factors affecting nutritional stunting among children under five years at Suhag Governorate. Methods: This study had been conducted at Suhag Governorate. The total number of the sample 1268 children who recruited through convenient sample. Results: Slightly less than half (49.1%) of the children were aged und 2 years. 53% of them were boys and 47% were girls,. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Similar results were found in a study done by Mahfouz and collaborators, in which prevalence was 19.1% in rural upper Egypt [10]. Additionally, a study done in Suhag, which is a southern Egyptian governorate revealed more moderate stunting in rural areas compared to urban ones, but the numbers were higher than the current study (25.6% and 21.6% respectively) [11]. Moreover, a study done among children and adolescents living in the Middle East and North Africa region revealed that the prevalence of stunting was 34.1% in rural and 12.4% in urban areas [12].…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were found in a study done by Mahfouz and collaborators, in which prevalence was 19.1% in rural upper Egypt [10]. Additionally, a study done in Suhag, which is a southern Egyptian governorate revealed more moderate stunting in rural areas compared to urban ones, but the numbers were higher than the current study (25.6% and 21.6% respectively) [11]. Moreover, a study done among children and adolescents living in the Middle East and North Africa region revealed that the prevalence of stunting was 34.1% in rural and 12.4% in urban areas [12].…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were found in a study done by Mahfouz and collaborators, which prevalence was 19.1% in rural upper Egypt [10]. Additionally, a study done in Suhag, which is a southern Egyptian governorate revealed more moderate stunting in rural areas compared to urban ones, but the numbers were higher than the current study (25.6% and 21.6% respectively) [11]. Moreover, a study done among children and adolescents living in the Middle East and North Africa region revealed that the prevalence of stunting was 34.1% in rural and 12.4% in urban areas [12].…”
Section: Discussionsupporting
confidence: 90%
“…However, the prevalence of under-weight were slightly higher in a study done by Shaban , Fahmy & Hassan in the year 2017, where, less than one fifth of the children had moderate underweight, and less than one tenth of them had severe underweight (Shaban, Fahmy, & Hassan, 2017). Moreover, according to Tanzania national nutritional survey in the year 2019, the prevalence of underweight were 14.6%, 3.5% were wasted while 0.4% were severely wasted and 2.8% were over-weight (Ministry of Health, Community Development, Gender et al, 2019).…”
Section: Table (8): Shows the Relationship Between Levels Of Dietary ...mentioning
confidence: 83%